Психологічні та гендерні кореляти агресивної поведінки у військовослужбовців - Пономаренко, Я. С.; Ponomarenko, Ya. S.; Греса, Н. В.; Hresa, N. V.; Філоненко, В. М.; Filonenko, V. M.; Пономаренко (Посохова) Яна Сергіївна; Володимир Філоненко; Греса Наталія Володимирівна (Вісник Харківського національного університету внутрішніх справ. – 2024. – № 2 (105), ч. 1. - С. 264-277, 2024)
Зазначено, що участь у конфліктах може значно впливати на прояв агресивності серед військовослужбовців, особливо серед тих, хто мав інтенсивний досвід у зонах активних бойових дій. У статті розглянуто ключові аспекти гендерної психології та вплив воєнних чинників на агресивну поведінку. Запропоновано термін «гендерно обумовлена агресивність». Вибіркою дослідження стали 89 військовослужбовців із числа комбатантів, серед яких 47 чоловіків та 42 жінки. Емпірично встановлено, що чоловіки мають вищу схильність до непрямої агресії та високий рівень недовіри, тоді як жінки виявляють меншу фізичну та вербальну агресію.

Participation in conflicts can have a significant impact on the manifestation of aggression among military personnel, especially those who have had intensive combat experience in war zones. The key aspects of gender psychology and the influence of military factors on aggressive behaviour are considered. The term “gender-based aggression” in military personnel is proposed, which reflects the concept that describes the difference in the manifestations of aggressive behaviour depending on the gender characteristics of a person. It is used to analyse and understand how gender and psychological factors influence the perception and expression of aggression among men and women, particularly in the context of military settings. The purpose of the study is to identify and analyse the psychological and gender factors associated with aggressive behaviour of military personnel. The study was conducted with 89 combatants, including 47 men (first group) and 42 women (second group). To achieve this goal, the Aggression Level Questionnaire by A. Bass and A. Darkey. The mathematical and statistical processing of the results was carried out using Student's t-test for independent samples and Fisher’s angular transformation criterion (φ). It has been empirically found that men have a higher tendency to indirect aggression and a high level of mistrust, while women show less physical and verbal aggression. The aggression index scores of both groups of servicemen are within acceptable norms, which indicates that the overall level of aggression among them is satisfactory. However, the hostility index score was higher than the normative values in both groups, indicating an increased tendency to hostile behaviour and conflict among servicemen. The results emphasise the importance of an individual approach to psychological support for servicemen and women, taking into account their gender identity. The findings of the study can serve as a basis for developing effective strategies for managing stress and conflict in the military environment and are an incentive for further research in the field of gender psychology.

Отмечено, что участие в конфликтах может оказывать значительное влияние на проявление агрессивности среди военнослужащих, особенно среди тех, кто имел интенсивный опыт в зонах активных боевых действий. В статье рассмотрены ключевые аспекты гендерной психологии и влияние военных факторов на агрессивное поведение. Предложен термин «гендерно обусловленная агрессивность». Выборкой исследования стали 89 военнослужащих из числа комбатантов, среди которых 47 мужчин и 42 женщины. Эмпирически установлено, что мужчины имеют более высокую склонность к косвенной агрессии и высокий уровень недоверия, тогда как женщины проявляют меньшую физическую и вербальную агрессию.
Psychological and gender specific correlates of aggressive behaviour in military personnel
Keywords: агресивна поведінка; агресивність; бойовий стрес; військовослужбовці; гендерно обумовлена агресивність; жінки; зона бойових дій; комбатанти; чоловіки; aggressive behaviour; aggression; combat stress; military personnel; gender-based aggression; women; combat zone; combatants; men; агрессивное поведение; агрессивность; боевой стресс; военнослужащие; гендерно обусловленная агрессивность; женщины; зона боевых действий; комбатанты; мужчины